ANALYSIS OF AGRICULTURAL ENTREPRENEURIAL INCOME AND ITS ROLE IN AGRICULTURE FINANCING. CASE STUDY ROMANIA - Alina MARCUTA; Liviu MARCUTA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Within the paper, an attempt is made to present an image regarding the evolution of the oil seed supply, in the Olt County, for the period 2015-2017. The processed information was extracted from a recognized database (www.insse.ro), highlighting the trends of establishment and evolution of the county's availability of seeds from species such as sunflower, rapeseed, soybeans etc. Olt County occupy the second place in the south-west Oltenia region. The cultivated area was 78,902.67 ha, the total production reached a level of 165,313.33 t, while the average production is characterized by a general level of 2,095 kg/ha.